Malaysian Exports To Middle Eastern Asian Countries (Meacs): The Role Of Halal Development (Hd) And Trade Agreement (Ta) - Azman, Nik Hadiyan Nik (2013)
Malaysia’s economic growths in the last three decades are mostly attributed to the success in exports sector. Export sector is dominated by manufacturing products such as electrical and electronics equipment, machinery, metal and mineral fuels. Among the top three Malaysian exports partners are United States, Singapore and Japan. Diversifying export destination is crucial so as to ensure that Malaysia will be reliant to selected few only. Thus, this study examines the bilateral export between Malaysia and Middle Eastern Asian countries (MEACs) for the period of 2002 to 2009 in order to investigate the potential impact of Halal development that is taking place in Malaysia on Malaysian exports.in addition this study also examine the impact of trade agreement on Malaysian export into MEACs. By using panel data, static effect, this study indicates that the crossrandom effect is the best model to be applied. The findings show that, the Halal development in certain extent play a vital role in promoting Halal products to MEACs, but it required more efforts to solve the pressing point. Besides, Trade Agreement has no threat of Trade Agreement diverting MEACs’ demand for import from Malaysia.